GENERAL CONCEPTS OF RISK INSURANCE IN INTERNATIONAL BUSINESS - Бєкєтов, Олександр В. (Journal of Strategic Economic Research, 2024)
In today’s globalized world, international business faces numerous risks that can significantly affect the financial stability and success of enterprises. Risks can arise from economic changes, political instability, currency fluctuations, natural disasters, cyber threats and other unforeseen circumstances. In the face of such uncertainty, the concept of risk insurance becomes critical to ensure business resilience and its ability to adapt to changing conditions. That is why the presented article examines the essence of risk and the conceptual principles of risk insurance in international business. The purpose of the work is to determine the general concepts of risk insurance in international business, as well as to determine the features of the risk insurance process in modern conditions of digitalization and transformational changes. Methods used in the work: methods of analysis and synthesis; methods of deduction and induction, method of comparison, logical method, morphological method, graphic method. The concept of risk insurance in international business encompasses a system of measures and tools that help companies manage potential losses, providing financial protection and minimizing possible negative consequences. Risk insurance not only provides protection against direct financial losses, but also facilitates strategic planning, increases business confidence and improves competitiveness. The main components of the concept of risk insurance in international business include: risk assessment, risk management strategies, insurance products, international standards and norms, analysis and monitoring, security, innovation. Therefore, the concept of risk insurance in international business is an important aspect of strategic management, which allows enterprises not only to protect themselves from possible financial losses, but also to ensure stability and adaptability in a rapidly changing global environment. Implementing effective risk insurance strategies helps companies move forward with confidence, reducing uncertainty and increasing their ability to operate successfully on the international stage.